Empowerment Of Salted Fish Sellers' Groups in Sungai Batang Ilir Village - Annisa Febriana; Restiana Kartika Mantasti Hapsari; Heryyanoor Heryyanoor; Nur Hikmah; Hidayah Putri; Muhammad Nor Arifudin; Ahmad Rizqo Abdillah; Zaini Ghani; Laily Rizky Anwar (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The salted fish processing and sales business is the main source of income for the people of Sungai Batang Ilir Village. The limited knowledge of salted fish processors and sellers regarding occupational health and safety (K3), entrepreneurship and business management, and online marketing branding is a barrier to improving the welfare of the salted fish seller group. Furthermore, this village is a flood-prone area that impacts business continuity and public health. This community service activity aims to increase the capacity of the salted fish seller group through training on occupational health and safety (K3), entrepreneurship and business management training, branding and online marketing management training, as well as education on flood disaster mitigation and other health education. The implementation method includes interactive lectures, demonstrations, mentoring, and pre- and post-test evaluations. The results of the activity showed an increase in participants' knowledge of 84% in K3 aspects, 80% in entrepreneurship, 80% in branding and online marketing, and 84% in flood disaster mitigation. In addition, participants were able to apply simple product branding and understand flood mitigation steps. This program is expected to become a model for community empowerment based on local potential with a multidimensional approach that integrates economic, health, and environmental aspects..